Case Report: A case series: heart rate variability during dental treatment with vasovagal reflex - Yamashita, Kaoru; Kibe, Toshiro; Yoshimine, Shusei; Uto, Akari; Uchino, Minako; Sugimura, Mitsutaka (Frontiers in Physiology, 2025)
IntroductionThe vasovagal reflex is the most frequent emergency that occurs during dental procedures, but its underlying mechanism is not understood. In this study, we conducted autonomic monitoring of patients with a history of vasovagal reflexes.Case descriptionWe focused on the high-frequency component, an indicator of parasympathetic activity, and interrupted the treatment when the high-frequency component increased. Treatment was then resumed after confirming that there was no mood disturbance and no increase in the high-frequency component. In another patient with a history of dental treatment-induced vasovagal reflex, autonomic activity during treatment was measured under atropine sulfate hydrate administration.DiscussionAnalysis of heart rate variability during the vasovagal reflex showed that parasympathetic hyperactivity was followed by sympathetic hyperactivity, indicating real-time changes in autonomic nervous system activity. In addition, the high-frequency component, which decreased after atropine sulfate hydrate administration, did not increase during treatment, along with the low-frequency to high-frequency ratio, a measure of sympathetic nervous system activity, and the vasovagal reflex did not occur. We believe that the visualization of a patient’s autonomic nervous system activity during dental treatment will improve the quality of systemic management and lead to the realization of a safe and comfortable treatment environment.